2020
DOI: 10.1017/s1368980020000130
|View full text |Cite
|
Sign up to set email alerts
|

A Nutrition Report Card on food environments for children and youth: 5 years of experience from Canada

Abstract: Objective:In 2014, a Nutrition Report Card (NRC) was developed as a sustainable, low-cost framework to assess the healthfulness of children’s food environments and highlight action to support healthy eating. We summarise our experiences in producing, disseminating, evaluating and refining an annual NRC in a Canadian province from 2015 to 2019.Design:To produce the NRC, children’s food environment indicator data are collected, analyzed and compiled for consensus grading by an Expert Working Group of researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Further, participants provided insight into the perceived barriers and facilitators that contribute to sustainable local food environment action. This study’s findings are supported by and build on our team’s experiences with the provincial NRC ( Ferdinands et al , 2020 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Further, participants provided insight into the perceived barriers and facilitators that contribute to sustainable local food environment action. This study’s findings are supported by and build on our team’s experiences with the provincial NRC ( Ferdinands et al , 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…LEAF is an ongoing community-based health promotion intervention implemented in 17 communities across Alberta, Canada, beginning in 2017. LEAF is one component of a multi-pronged research project, under the umbrella of an annual assessment of the province’s food environments and nutrition policies, Alberta’s Nutrition Report Card on Food Evironments for Children & Youth (provincial NRC), which assesses the status of five food environments ( Brennan et al , 2011 ): the physical (what food is available), communication (food and nutrition messages), economic (food affordability), social (norms and values about food) and political (rules and policies) environments [see Olstad et al ( Olstad et al , 2014 ) for details, and Ferdinands et al ( Ferdinands et al , 2020 ) for progress since its implementation in 2015]. Engaging local communities represented a supplemental opportunity to improve provincial food environments.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies provide insight into the complexities and challenges of building community relationships while conducting citizen science research, which are best demonstrated through a closer examination of the category treading lightly. Based on our experiences with the provincial NRC [ 18 ], we expected that communities might have some concerns with assigning grades to community settings. However, we did not anticipate that these concerns would lead communities to alter the LEAF process.…”
Section: Discussionmentioning
confidence: 99%
“…Although each “community” in this study was a municipality of varying size (see Table 1 ), we refer to LEAF as a community-based intervention because it could be implemented to align with other definitions of community. Part of a broader provincial strategy, which includes the Alberta Nutrition Report Card on Food Environments for Children and Youth (provincial NRC) [ 18 ], LEAF employs a “by the people” citizen science approach [ 12 ] to engage residents in monitoring and acting on local food environments and nutrition policies relevant to children and youth. Following Brennan et al [ 19 ], LEAF evaluates five food environments: the physical, communication, economic, social, and political environments.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, research on how food environments shape the availability, affordability, and social acceptance of food and nutrition choices is growing. Nutrition report cards have been developed to assess the healthfulness of children’s food environments [ 46 ] and could be applied to key environments for people with T2D to support healthy eating in this population.…”
Section: Discussionmentioning
confidence: 99%